NILAI TAMBAH DAN BAURAN PEMASARAN PRODUK AGROINDUSTRI JAMUR TIRAM PUTIH PADA RUMAH JAMUR NANDO KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Lia Syafridayanti; Septina Elida (DINAMIKA PERTANIAN, 2024)
White oyster mushrooms have significant potential for enhancement and better negotiating power through agro-industrial initiatives. This study seeks to examine the added value generated from processing white oyster mushrooms into various products, including crispy mushrooms, mushroom nuggets, and mushroom rendang, along with their marketing strategies. The research focuses on the "Nando Mushroom House," a home industry located in the Tenayan Raya District of Pekanbaru City. Data were analyzed using straightforward statistical techniques, employing both descriptive and quantitative methods. The findings revealed that: 1) among the processed products, mushroom nuggets offered the highest added value, followed by crispy mushrooms and mushroom rendang. 2) (i) Product: Crispy mushrooms and mushroom rendang feature appealing packaging and trademarks, while mushroom nuggets remain in simple packaging. (ii) Price: The prices of crispy mushrooms, mushroom nuggets, and mushroom rendang are generally affordable, with various product sizes available. (iii) Place: Crispy mushrooms, mushroom nuggets, and mushroom rendang are exclusively sold at mushroom tourism sites. (iv) Promotion: Marketing for crispy mushrooms, mushroom nuggets, and mushroom rendang is conducted through online platforms.